Influence of Simultaneous Doping of Tl on the Transition Temperature Tc and the Lattice Parameters of HgBa2Ca2Cu3O8+ Î´ Superconductors - Jassim, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the present study, we have reported investigations on the effect of simultaneous substitution of Tl at the Hg site in the oxygen deficient HgOÎ´ layer of Hg1-xTlxBa2Ca2Cu3O8+ Î´ cuprate superconductor. Bulk polycrystalline samples were prepared by the two-step solid state reaction process. It was observed that the grown Hg1-xTlxBa2Ca2Cu3O8+ Î´ corresponds to the 1223 phase. Electrical resistivity, using four probe technique, is used to find the transition temperature Tc. The highest Tc(0ffset) were 108, 102,113, 118, 125 and 121K for Hg1xTlxBa2Ca2Cu3O8+ Î´ with x = 0.0, 0.05, 0.10, 0.15, 0.20 and 0.25 respectively. The optimum Tc(off) of ~ 125 K and Tc(onset) ~ 136K   was found for the composition Hg0.80Tl0.20Ba2Ca2Cu3O8.293. All the samples preparation with O2 flow, we found that the O2 flow in our samples produce high- Phase superconductors.        X-ray diffraction(XRD) analysis showed a pseudotetragonal structure with an increase of the c-axis lattice constant for the samples doped with Tl as compared with these have no Tl content. It was found that the change of  the Tl  concentrations of all our samples produces a change in the Mass density Ïm, c/a and volume fraction VPh(1223).